(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The language, as the mirror of the nation, plays an important role in the development of the country. History has seen in a long time for countries being conquered, nations being tortured, cultural and economic infrastructure being destroyed. However, language loss could bring much more devastating outcomes. It is not a secret that language, as a linguistic phenomenon, has a great impact on the society. The growing generation is truly obsessed with massive information flood that comes from the latest communication means due to the globalization. In fact, it is becoming more difficult to preserve national heritage of the community. Being one of the most important of cultural heritage of the nation, this linguistic phenomenon cannot be neglected [3].